Sustained-Release Corticosteroid Options - Cabrera, Mariana (Hindawi Publishing Corporation, 2014)
Sustained-release corticosteroid treatment has shown to be a promising strategy for macular edema due to retinovascular disease (i.e., diabetes and retinal vein occlusion) and for the treatment of noninfectious posterior uveitis. Clinicians now have the option of three sustained-release corticosteroid implants: Ozurdex (Allergan Inc., Irvine, CA) which releases dexamethasone and two devices that release fluocinolone acetonide, Retisert (Bausch & Lomb, Rochester, NY), and Iluvien (Alimera Science, Alpharetta, GA). Each has different physical characteristics and duration effect and has been approved for different indications. Herein we provide a summary of the current clinical knowledge regarding these implants.